Analisis Pengaruh Variabel Makroekonomi terhadap Return Kelompok Saham Subsektor Perkebunan - Dirga, Satria Prawira; Siregar, Hermanto; Sinaga, Bonar M (Jurnal Aplikasi Manajemen, 2016)
this studyanalyze the effect of the movement of macroeconomic variables (SBI, exchange rate, inflation, oil prices and Composite Stock Price Index (JCI)) and predict the stock price of the individual returns and return a proxy INDEX in plantation sub-sector. This study used the analytical techniques of multifactor APT model of equation (Multivariate Regression Model) to determine the effect of macroeconomic variables on stock returns in plantation sub-sector group. Furthermore,the formation of the share price index estimation model APT as a proxy (proxy INDEX) was done. Methods Vector Error Correction Model (VECM) was used to study the response of stock returns and risk to changes in macroeconomic variables. Factor in world oil prices and a significant negative effect on stock returns AALI, LSIP, SGRO, SMAR, TBLA, UNSP and return the proxy INDEX. exchange rates factors provide a positive and significant affect to stock returns AALI, LSIP, SMAR, TBLA and return the proxy INDEX. SBI Factors had a significantly negative affect to the return TBLA, while the SBI had positive affect to return AALI, SMAR and return the proxy INDEX. Inflation factor had a significantly positive effect to returns TBLA and had a significantly negative effect to the change in return INDEX proxy. Agricultural index and JCI index had a significantly positive effect to stock returns AALI, LSIP, SGRO, SMAR, TBLA, UNSP and return the proxy INDEX.